Junior Intern’s Perceptions of Professionalism Education in Post-Graduate Medical Program at Medical Faculties in Cimahi and Bandung - Ali Taufan; Ris Kristina; Moch. Alif Rois (Sean Institute, 2025)
Professionalism is one of the competencies of a doctor in Indonesia. One of the ways to become a professional doctor is to undergo a good medical education. Medical education is divided into two stages, namely the undergraduate and professional education stages. Professionalism learning is divided into two methods, namely the learning method and evaluation of professionalism learning. This study aims to determine the perceptions of Junior Intern towards professionalism education at the professional education stage at the Faculty of Medicine in Cimahi and Bandung. This research method is descriptive observational with accidental sampling technique with a total of 94 Junior Intern as respondents, with data collection used a questionnaire. The results of this study provide an overview regarding the knowledge of Junior Intern regarding professionalism learning methods of 63.3%. While the professionalism learning method that has been applied is 70.6% the formal learning method. The results of the study also provide an overview of Junior Intern knowledge of professionalism learning evaluation methods, the observed clinical encounter method was 45.4%. The evaluation method that has been applied in the Faculty of Medicine in Cimahi and Bandung is observed clinical encounter at 47.5%. The results of the study show that the majority of professionalism learning methods that is known and has been applied in the Faculty of Medicine in Cimahi and Bandung is a formal method, but there are still those who do not know about professionalism learning methods. The majority of the evaluation of professionalism learning methods that are known and have been applied are observed clinical encounter.